Expanded foams from potato starch reinforced by malt pomace (Research, Society and Development, 2020)
The objective was to develop and characterize expanded foam based on potato starch reinforced with malt pomace. Foams were designed by thermal expansion in closed mold, using a factorial design 22, evaluating the effect of glycerol and malt pomace content on moisture, water activity, thickness, density, water absorption capacity (WAC) and tensile strength. The addition of malt pomace resulted in foams with less thickness and consequently higher densities. Only the CAA response had significant difference, observing the higher glycerol contents the higher CAA contents. The presence of malt pomace did not improve the resistance of the foams. The test comprising of 30% (w/w) of pomace and 2.5% (w/w) of glycerol was more favorable to be applied as food packaging as it presented low moisture (9.42%), thickness of 3.65 mm, low density (0.33 g cm-3) and water activity (0.477), these parameters being desirable for the proper preservation of packaging and food.